Integrated Financial Management System and Financial Reporting Effectiveness: A Case of Tororo District Local Government - Patrick Oketcho (Uganda Christian University, 2024)
Generally, the objective of implementing Integrated Financial Management Information System (IFMIS) is to increase the effectiveness and efficiency of state financial management and facilitate the adoption of modern public expenditure practices in keeping with international standards and benchmarks. The main objectives of the study was to analyse the effectiveness of cash management and budgeting systems; financial reporting systems in IFMIS; internal control systems in IFMIS; and the effectiveness of organisational accountability systems in IFMIS on financial management in public sector in Uganda. The study adopted a descriptive research in this study with a targeted population of 18 National Government Ministries in Uganda. The primary data was collected using questionnaire that relates to specific objectives of the study. Secondary data involved past reports such as annual budget data, progress reports and internal audits reports since the system implementation started and had key information that will be helpful to the research study. The study used both quantitative and qualitative method of data analysis. Collected data was first coded and then quantitatively analysed according to statistical information derived from the research questions. Secondary data were derived from desk review of annual information on IFMIS for all variables for a period of three years (2013-2015). The study found that organizational accountability systems, cash management and budgeting systems, internal control systems and financial reporting systems positively and significantly influenced the financial management in the public sector. The study recommends that managers can use this information to plan and formulate budgets; examine results against budgets and plans; manage cash balances; track the status of debts and receivables; monitor the use of fixed assets and monitor the performance of specific departments or units.
Undergraduate Research